(untitled) (Research, Society and Development, 2021)
Leishmaniasis is a parasitic disease that affects populations around the world, especially those in developing countries. Available therapy has serious adverse effects and reports of resistant strains are recurrent. Thus, mapping information on the antiparasitic activity of plants and secondary metabolites for the treatment of leishmaniasis becomes a relevant process for systematizing the studies and technologies developed with these natural products. Thus, this article aimed to carry out a scientific and technological survey of the species Pilocarpus microphyllus and the alkaloid epiisopiloturine (EPI) in databases of publication of articles and patent deposits. For this, the following keywords were used, with the boolean operator AND, in the searches: “Pilocarpus microphyllus”, “epiisopiloturine”, “epiisopiloturine” and “Leishmania amazonensis”. The results showed that most articles and patents involve the keyword “Leishmania amazonensis” (>95% for articles, >89% for patents) and elucidate the search for new therapeutic agents that can replace or enhance the anti-leishmania effect of drugs already used. Searches for the keyword “Pilocarpus microphyllus” show that publications and patents explore the use of the plant and the alkaloids of this jaborandi in biological applications, with only one patent filing using the plant in the treatment of leishmaniasis. For the epiisopiloturine alkaloid, four articles already prove the antiparasitic potential of EPI, and only one patent evidences the application of the alkaloid with antileishmanial activity. Therefore, it is concluded that the researches developed with P. microphyllus and EPI make the scientific and technological scenario promising for the development of antileishmania studies and technologies.